Effects of Political Consumerism on Consumer Behavior in the U. S. Automobile Market - Isaac H. Desta; Brendon Shibley (STIE Malangkucecwara, 2017)
The effects of political consumerism on consumer behavior is not clearly established in the automobile industry despite its growing significance in the United States. Therefore, this paper seeks to illustrate the increasing role of political consumerism in the car industry. To accomplish this goal, the relationship between political affiliations, consumer ratings of vehicles, car preference and purchasing decisions are explored. To this end, a random sample of 104 undergraduate students at Holy Cross College, Notre Dame, Indiana, USA were selected. By using MANOVA and OLS regression statistical models, the paper illustrates that political ideology significantly predicts consumer behavior of this cohort. Specifically, Republicans prefer to buy Ford, rate Ford vehicles higher than Democrats and generally own domestic vehicles. On the other hand, Democrats prefer to buy Toyota, rate Toyota vehicles higher than Republicans and generally own foreign vehicles. However, there is no significant statistical difference between Democrats and Republicans in regards to their perception of the performance of Toyota and Ford cars. Further, personal (student) income reinforces the influence of political ideology on consumer behavior